Dampak Kebijakan Dividen terhadap Harga Saham pada Waktu Ex-dividend Day - Pujiono Pujiono (The Indonesian Journal of Accounting Research, 2013)
The ex-dividend day is right lost day of dividend that will pay from company to stocks holder. This research is designed to examine capital markets reaction at the ex-dividend day in Indonesia and Singapore Capital Market. Research variables are a closing stocks price at the ex-dividend day as dependent variable, and dividend, trading volume, and financial leverage as independent variables.The collecting data uses purposive sampling. One thousand and fifty two data are collected from three hundred and thirty nine companies listed in Jakarta Stock Exchange, and three hundred and ninety data are collected from three hundred and forty three companies listed in Singapore Stock Exchange during in 1992-1996. Several statistical tests of this research use classical assumption test, feasibility model test, and hypothesis test.The result of research showed that all variables are statistically significant. However, for the sampli is in Indonesia only succeed to support second hypothesis, and for the sampli is in Singapore succeed to support first and third hypothesis. The conclusion of research that market reaction of the ex-dividend day has had different impact between developed capital market and emerging capital market.